Epidemiology of gymnastics injuries - Wolf, S. F.; LaBella, C. R. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
Gymnastics is a popular sport both in the United States (USA) and internationally. According to the Federation Internationale de Gymnastique or the International Gymnastics Federation (FIG), approximately 50 million people worldwide participate regularly in club gymnastics. In the United States, approximately 3.3% (estimated 984,000) of children ages 6-12 participate in gymnastics on a regular basis. Gymnastics contains eight disciplines: Men`s Artistic, Women`s Artistic, Rhythmic, Trampoline, Acrobatic, Aerobic, Gymnastics for All, and Parkour. In the United States, athletes can participate in a variety of settings including club/USA Gymnastics Junior Olympic (USAG JO) program, high school teams, National Collegiate Athletic Association (NCAA) teams, national/international elite level, and the Olympics.